IMPLEMENTASI SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) PADA PT. INTI BENUA PERKASATAMA KOTA DUMAI - Wan Aditya Fadli; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The title of this research is the implementation of Safety Management System and Occupational Health at PT. Inti Benua Perkasatama Dumai City. The background of this study is the number of incidents of accidents that occur in the PT. Inti Benua Perkasatama Dumai City when the government has issued Law No. 1 of 1970 on Safety and Health at work and the Regulation of the Minister of Labor number 05 of 1996 on Occupational Safety and Health Management aims to minimize the occurrence of accidents. To ensure the safety and health of workers and others who are in the workplace, as well as sources of production, production process, and the work environment in a safe state, should the application of the Occupational Safety and Health Management System (SMK3). The core purpose of an application SMK3 is to provide protection to workers. However, the worker is a corporate asset that should be preserved and maintained safety. The purpose of this study was to describe the implementation of safety management systems and occupational health at the PT. Inti Benua Perkasatama by Minister of Manpower Regulation No. 05 of 1996 and describe any efforts undertaken by the company to minimize factors and potential hazards. This is a qualitative study using the method of direct observation of spaciousness, the informant interviews Head of Section K3 Disnakertrans Dumai, Public Relations of PT. Inti Benua Perkasatama, secretary P2K3 PT. Inti Benua Perkasatama as well as the core part of the production employees of PT. Inti Benua Perkasatama Dumai City. From these results it can be concluded that the application of the Occupational Safety and Health Management System (SMK3) have not been going well and in accordance with the ministerial decree number PER 05 / MEN / 1996. Implementation still needs to be improved because there is still a shortfall, especially at the stage of inspection and evaluation. Because they inspection and evaluation is still deemed not work effectively, the company also does not have documented procedures in employee skill enhancement training, and incident reporting mechanisms K3 which also does not have documented procedures. Keyword: Implementation, Occupational Safety and Health Management System (SMK3)